Hajj Manasik Training For Prospective Pilgrims: A Communal Religious Empowerment Approach - Taufikin, Taufikin (SIMAS: Jurnal Pengabdian Masyarakat, 2025)
The Hajj rituals training activity in Demak Regency in 2025was motivated by the low technical and spiritualunderstanding of prospective pilgrims (JCH) of the correctprocedures for Hajj according to Sharia guidance. Involving1,200 participants, this activity used a communal religiousempowerment approach based on Participatory ActionResearch (PAR) during Ramadan 1446 H/2025 M, heldcentrally at the IPHI Building in Demak Regency. The mainobjectives of the activity were to improve Hajj literacy andmental-physical readiness and strengthen social cohesionamong pilgrims. The activities were carried out in threestages, including briefing on the theory of Hajj fiqh, technicalpractices and simulations, and spiritual-motivationalstrengthening. Evaluation was conducted through pre-testand post-test as well as direct observation. The resultsshowed significant improvements in fiqh understanding,psychological readiness, and the formation of small supportgroups among pilgrims. This training indicates a communaland structured approach can create optimal worshipreadiness and strengthen religious solidarity. This model willbecome a national reference in sustainable communitybased Hajj pilgrimage coaching.